Cross-Country Inequality Trends - Daron Acemoglu (Luxembourg Income Study (LIS), 2002)
The economics profession has made considerable progress in understanding the increase in wage inequality in the U.S. and the UK over the past several decades, but currently lacks a consensus on why inequality did not increase, or increased much less, in (continental) Europe over the same time period. I review the two most popular explanations for these differential trends: that relative supply of skills increased faster in Europe, and that European labor market institutions prevented inequality from increasing. I argue that these two explanations go some way towards accounting for the differential cross-country inequality trends, but do not provide an entirely satisfactory explanation. In addition, it appears that relative demand for skills increased differentially across countries. Motivated by this reasoning, I develop a simple theory where labor market institutions creating wage compression in Europe also encourage more investment in technologies increasing the productivity of less-skilled workers, thus implying less skill-biased technical change in Europe than in the U.S.
Keywords: 330; Einkommensverteilung; Lohnstruktur; Bildungsertrag; Qualifikation; USA; Großbritannien; Europa